2015
DOI: 10.4269/ajtmh.15-0162
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Evaluation of the Posttreatment Prophylactic Effect of Dihydroartemisinin–Piperaquine Versus Artemether–Lumefantrine for First-Line Treatment of Plasmodium falciparum Malaria Across Different Transmission Settings in Africa

Abstract: Abstract. Malaria disproportionately affects young children. Clinical trials in African children showed that dihydroartemisininpiperaquine (DP) is an effective antimalarial and has a longer posttreatment prophylactic (PTP) effect against reinfections than other artemisinin-based combination therapies, including artemether-lumefantrine (AL). Using a previously developed Markov model and individual patient data from a multicenter African drug efficacy trial, we assessed the economic value of the PTP effect of DP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…falciparum malaria in an Italian tourist returned from Ethiopia [ 51 ]. Post-treatment prophylactic effect of DHA-PPQ against re-infections is considered longer than that of AL [ 52 ]. In Ethiopia DHA-PPQ failures have not been reported before.…”
Section: Discussionmentioning
confidence: 99%
“…falciparum malaria in an Italian tourist returned from Ethiopia [ 51 ]. Post-treatment prophylactic effect of DHA-PPQ against re-infections is considered longer than that of AL [ 52 ]. In Ethiopia DHA-PPQ failures have not been reported before.…”
Section: Discussionmentioning
confidence: 99%
“…This intervention showed a cost of $5 per DALY averted. Three of the reviewed studies compared the cost-effectiveness of dihydroartemisinin–piperaquine (DP) and artemether–lumefantrine (AL) in treatment of complicated malaria [ 21 , 23 , 55 ]. The maximum cost per DALY averted for these three studies was $12.54.…”
Section: Resultsmentioning
confidence: 99%
“…It was predicted that DP was more cost-effective compared to AL with the assumption that compliance to treatment was higher in DP than in AL due to the once a day dose for DP [ 23 ]. It was also suggested that DP might be more cost effective than AL across a range of settings in Africa [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5] From a preventive point of view, the long half-life of the partner drug piperaquine conveys protection of 22 days for adult patients and around 20 days for paediatric patients, 2 indicating a better post-treatment prophylactic eff ect than other combination therapies. 3,6,7 In the Lancet Infectious Diseases, Julie Gutman and colleagues analyse the safety, tolerability, and effi cacy of repeated doses of DP, for the treatment and prevention of malaria, with a particular focus on its use as intermittent preventive treatment (IPT). 8 Their meta-analysis, looking at over 4000 patients exposed to repeated courses of DP, substantiates the high effi cacy of this drug in terms of controlling malaria and all-cause hospital admission, and the good tolerability of repeated treatment schemes, with no evidence of arrhythmias secondary to the potential QT prolongation eff ect of cumulative doses of piperaquine after repeated doses.…”
Section: Dihydroartemisinin-piperaquine: If It Work For Control Canmentioning
confidence: 99%